Poland: Monetary Policy Still Outside the Eurozone - Mikos-Sitek, Agnieszka (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
Poland is an EU Member State that has not adopted the single currency status and remains outside the Eurozone. It has also not yet joined the European Banking Union based on the so-called ‘close cooperation’. In the European integration process, numerous measures were taken to align Polish legal solutions in the banking field with European Union regulations. Among other things, the introduced changes concerned the functioning of the central bank of the state and led to its inclusion in the single monetary and currency policy of the European System of Central Banks. Despite growing expectations in recent years that Poland will soon adopt the euro, Poland has not taken decisive steps in this regard due to its ambiguous assessment of the benefits and possible risks involved. It should also be noted that Poland’s accession to the Euro area is not currently possible because of its insufficient fulfilment of the convergence criteria. Further, Poland’s decision to function in the euro area is complicated by the specific predispositions of the Polish banking sector as well as by the uncertain timeline for adopting a single currency due to the ongoing economic crisis. Keywords: central bank, monetary policy, banking union, monetary policy tools, European integration